ANALISIS REPRESENTASI GAMBAR DALAM MENYELESAIKAN PERMASALAHAN PEMANTULAN DAN PEMBIASAN BAGI MAHASISWA PROGRAM STUDI PENDIDIKAN FISIKA - Murtono . (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2015)
Reflection and refraction of light propagation always take advantage of the depiction. To understand the concepts of reflection and refraction can be done by describing the reflected ray and rays refracted ray if the boundary of an object field of optics . The purpose of this study was to diagnose mastery of concepts students about the concept of reflection and refraction through the representation of the image . The study was conducted by giving a matter against 40 students who have taken Physics Education course Fiska Basic II . Problem consists of six items ray images come in different shapes optical object , then the student completed the reflected rays and refraction rays after the optical boundary . The analysis was based on the answers of students in the form of image refraction and reflection.